Is Hematopoietic Clonality of Indetermined Potential a Risk Factor for Pulmonary Embolism? - Soudet, S.; Jedraszak, G.; Evrard, O.; Marolleau, J.P.; Garcon, L.; Pietri, M.A. Sevestre (TH Open, 2021)
Background Unprovoked pulmonary embolism (uPE) is a severe and frequent condition. Identification of new risk factors is mandatory to identify patients that would benefit from a long-term treatment. Clonal hematopoiesis of indeterminate potential (CHIP) is defined by the acquisition of somatic mutations that drive clonal expansion in the absence of cytopenia. Its prevalence is estimated of 5% in the population above 65 years. Since inflammation and endothelial dysfunction may share a pathophysiological pathway(1), we hypothesized that CHIP, may be a risk factor for uPE.Methods We conducted a pilot retrospective observational study. Patients with iPE between 18 to 65 years old were included. PE was considered as unprovoked, when no transient nor persistant risk factor was present and when thrombophilia testing was negative. We excluded documented atherosclerosis, personal or familial history of VTE and presence of cytopenias. CHIP proportion in uPE patients were analyzed using next generation sequencing of the coding sequence of a custom panel composed by DNMT3A, ASXL1, SF3B1, TET2 and TP 53.Results Upon 61 patients with uPE consecutively included, a total of 19 somatic mutations were found in 12 patients (20%) IC95% [10 - 20]. 15 mutations were found in DNMT3A gene, 3 in ASXL1 and one in TET2. There was no diference in terms of age, PE location, DVT presence and risk stratification in CHIP carriers and non carriers.Conclusion We report for the first time, the presence of high rates of CHIP in patients presenting with uPE. Thus, CHIP may be a new risk factor for VTE. These results need to be confirmed in an ongoing prospective case-control study including more patients and using a more diverse gene panel to better determine CHIP incidence in uPE.
Keywords: gene mutations; pulmonary embolism; venous thrombosis